Development of Soil Loss Erosion Forecasting Using the Revised Universal Soil Loss Equation and Geographic Information System - Ishak N.A.; Mohd Sidek L.; Yalit M.R.; Razad S.K.A.Z.A.; Sinnakaudan S.A.; Aziz A.M.A. (Springer, 2023)
Large-scale development in the upstream area has a catastrophic impact on soil erosion on the surrounding community and property in Cameron Highland. The massive land-use activities give a negative impact if inadequate protection of assets cannot be controlled which led the sedimentation issue to each reservoir in Cameron Highland. Therefore, this research was conducted to forecast the source of soil erosion and sedimentation rate using the Revised Universal Soil Loss Equation (RUSLE) empirical model technique in the integration of Geographic Information System (GIS). Spaceborne IFSAR with an accuracy of 5m was used and generated Digital Elevation Model (DEM) for terrain and elevation conditions. Rainfall Erosivity (R), Soil Erodibility (K), Topographic (LS), Cover Management (C), Support Practice (P) are the factors need to be included in the RUSLEs formula. The annual rainfall data of 11 rainfall stations were used in the study for modeling the R factor, an average annual amount of rainfall was collected from the year 2007 until 2017. Land use maps comprising three different years namely; 2003, 2006 and 2017 have been used to calculate the C factor and P factor. The result indicated that the rate of potential soil loss was increased by almost 94.8% between 2006 and 2017. Sediment yield was expected to be higher due to an increment of soil loss in the year 2003, 2006 and 2017. The sediment yield for Sultan Abu Bakar Dam situated at Ringlet Reservoir was indicated 349,633.99m3/year in 2003, whilst 142,970.71m3/year in 2006 was expected to decrease after 2003 where recorded 59% of reduction. Subsequently, the sediment yield rate was projected to increase by about 56% or 331,449.01m3/year in 2017. Hence, these findings have significant implications for soil loss and sediment yield because of major land-use changes which depend on topography and rainfall factor. 2020, Springer Nature Singapore Pte Ltd.